Integrasi Teknologi Informasi di Pesantren Dalam Upaya Meningkatkan Keterampilan Digital, Kualitas Pembelajaran dan Kepedulian Penghijauan - Mesran, Mesran; Suginam, Suginam; Dwika Assrani (Forum Kerjasama Pendidikan Tinggi, 2024)
This article discusses the integration of information technology in Islamic boarding schools as an effort to improve digital skills, learning quality, and concern for greening among teachers. This research aims to identify and implement effective strategies in using information technology in the Islamic boarding school environment to support a more modern and efficient teaching and learning process. Through a case study approach, this research involved a number of teachers in several Islamic boarding schools who were selected purposively. The methods used include observation, in-depth interviews, and questionnaires to collect data on teachers' digital knowledge and skills, as well as their attitudes towards greening. The research results show that the integration of information technology can significantly improve teachers' digital skills, which in turn contributes to improving the quality of learning. The teachers involved in this research reported increased abilities in operating learning software, using e-learning platforms, and using social media for educational activities. In addition, this research found that the use of information technology can also increase teachers' awareness and concern for environmental issues, especially greening, by utilizing digital applications and platforms for greening campaigns and environmental education. The implementation of information technology in Islamic boarding schools not only improves the quality of learning and digital skills, but also broadens teachers' insight into the importance of protecting the environment. This article recommends ongoing training and the provision of adequate technological infrastructure in Islamic boarding schools to support the development of digital skills and environmental awareness. It is hoped that this integration can create a better and more sustainable educational ecosystem in Islamic boarding schools, with teachers as the main agents of change.